Administration of erythropoietin in patients with myocardial infarction: does it make sense? An updated and comprehensive meta-analysis and systematic review - Ali-Hassan-Sayegh, Sadegh; Mirhosseini, Seyed Jalil; Tahernejad, Mahbube; Mahdavi, Parisa; Haddad, Fatemeh; Shahidzadeh, Azadeh; Lotfaliani, Mohammad Reza; Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Weymann, Alexander; Sabashnikov, Anton; Popov, Aron-Frederik (Cardiology research and practice, 2015)
This systematic review with meta-analysis sought to determine protective effects of erythropoietin on clinical outcomes following percutaneous coronary intervention (PCI). Medline, Embase, Elsevier and Sciences online database as well as Google scholar literature were used for selecting appropriate studies with randomized controlled design. The effect sizes measured were odds ratio (OR) for categorical variables and weighted mean difference (WMD) with 95% confidence interval for calculating differences between mean values of duration of hospitalization in intervention and control groups. Values of P<0.1 for Q test or I2>50% indicated significant heterogeneity between the studies. The literature searches of all major databases retrieved 973 studies. After screening, a total of 15 trials that reported outcomes were identified. Pooled analysis was performed on left ventricular ejection fraction (WMD of −0.047; 95% CI: −0.912 to 0.819; P=0.9), left ventricular end diastolic volume (WMD of −0.363; 95% CI: −3.902 to 3.175; P=0.8), left ventricular end systolic volume (WMD of 0.346; 95% CI: −2.533 to 3.226; P=0.8), infarct size (WMD of −0.446; 95% CI: −2.352 to −1.460; P=0.6), stroke (OR of 2.1; 95% CI: 0.58 to 7.54; P=0.2), re-myocardial infarction (OR of 1.06; 95% CI: 0.52 to 2.185; P=0.8), heart failure (OR of 0.53; 95% CI: 0.259 to 1.105; P=0.09), mortality (OR of 0.56; 95% CI: 0.27 to 1.19; P=0.13), thrombosis (OR of 0.774; 95% CI: 0.41 to 1.45; P=0.4), major adverse cardiovascular events (OR of 0.926; 95% CI: 0.63 to 1.35; P=0.6). Short-term administration of EPO in patients with myocardial infarction (MI) undergoing PCI does not result in improvement in cardiac function, reduction of infarct size and all-cause mortality. Low dose EPO therapy may not be the choice of treatment for the patients with MI, while higher doses might be more effective.